Politik Ke-Minahasaan dari Waktu Ke Waktu: Perspektif Strukturasi. - Kimbal, Alfon (Sam Ratulangi University, 2015)
Abstract : the presence of the new local elites to be threat for structure has been established through newsocial practices they trying to do. Through that social practices, new local elites trying to derutinisasi oldhabits to be new structure allow dominance and their legitimacy. This article purpose to reaffirmed socialchange facts always inherent on the building ethnic and politic in Minahasa. Especially be related withthe power context inside it.Western civilization in terms of education and religion to give modalities for the christian actor toderutinisasi old structure their according to mistakenly. Because conducted a massive and continuous,action of derutinisasi reap success in shaping the structure of christianity on the groud of Minahasa.After the opening tap democratic new order evidently to result the another interesting phenomenon. Thetrend of revival ethnic identity sticking to the surface, also happened in Minahasa. The traditionalstructures trying to repeat past power.Keywords : Politic, Perspective Structure, Minahasa